PENGARUH KEBIJAKAN DIVIDEN, PROFITABILITAS DAN LIKUIDITAS TERHADAP KEBIJAKAN HUTANG - Putri Jesica Pratiwi; Mediya Destalia; M. Iqbal Harori (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
Abstract This study aims to examine the effect of dividend, profitability, and liquidity policies on debt policy in manufacturing companies listed on the Indonesia Stock Exchange for the period 2017–2021. The data collection technique in this study used a purposive sampling technique and obtained a sample of 27 companies. Using the Eviews 12 program test tool, the data analysis technique employs multiple regression analysis of panel data models. The research results show that partially dividend policy and profitability variables had no significant effect on debt policy, while the liquidity variable had a significant effect on debt policy. According to the simultaneous F test, the dividend policy, variables of profitability, and liquidity have a concurrent influence on debt policy.